Identifying volatile and non‐volatile organic compounds to discriminate cultivar, growth location, and stage of ripening in olive fruits and oils. (17th February 2022) - Greco, Maria; Spadafora, Natasha; Shine, Martin; Smith, Ann; Muto, Antonella; Muzzalupo, Innocenzo; Chiappetta, Adriana; Bruno, Leonardo; Müller, Carsten; Rogers, Hilary; Bitonti, M. Beatrice
Abstract: BACKGROUND: There is increasing consumer demand for olive oil to be traceable. However, genotype, environmental factors, and stage of maturity, all affect the flavor and composition of both the olives and olive oil. Few studies have included all three variables. Key metabolites include lipids, phenolics, and a wide range of volatile organic compounds (VOCs), which provide the olives and oil with their characteristic flavor. Here we aim to identify markers that are able to discriminate between cultivars, that can identify growth location, and can discriminate stages of fruit maturity. 'Nocellara messinese' and 'Carolea' olive fruits were grown at three locations differing in altitude in Calabria, Italy, and harvested at three stages of maturity. Oil was analyzed from the two most mature stages. RESULTS: Nine and 20 characters discriminated all fruit and oil samples respectively, and relative abundance of two fatty acids distinguished all oils. Whole VOC profiles discriminated among the least mature olives, and oil VOC profiles discriminated location and cultivar at both stages. Three VOCs putatively identified as hexanal, methyl acetate, and 3‐hexen‐1‐ol differentiated all samples of oils from the most mature fruit stage. CONCLUSION: The results confirm that interactions of location, cultivar and fruit maturity stage are critical for the overall pattern of aroma compounds, and identify potential markers of commercial relevance. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.